2012
DOI: 10.1667/rr2868.1
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Exosomes Containing RNA in Mediating Nontargeted Effect of Ionizing Radiation

Abstract: Communication between irradiated and un-irradiated (bystander) cells can cause damage in cells that are not directly targeted by ionizing radiation, a process known as the bystander effect. Bystander effects can also lead to chromosomal/genomic instability within the progeny of bystander cells, similar to the progeny of directly irradiated cells. The factors that mediate this cellular communication can be transferred between cells via gap junctions or released into the extracellular media following irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 41 publications
3
116
1
Order By: Relevance
“…Our recent work showed that EVs mediate BE following irradiation (48,67). Subsequent findings have confirmed that EVs mediate BE following different stresses, including radiation (48,49,67) and heat shock (59).…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Ressupporting
confidence: 52%
“…Our recent work showed that EVs mediate BE following irradiation (48,67). Subsequent findings have confirmed that EVs mediate BE following different stresses, including radiation (48,49,67) and heat shock (59).…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Ressupporting
confidence: 52%
“…The role of exosomes in mediating nontargeted effects in MCF7 breast cancer cells has been reported in a recent study (37) where exosomes were shown to be involved in radiation induced bystander effects and genomic instability. DNA damage was measured after addition of conditioned media to MCF7 cells and RNase was found to abrogate this DNA damage, indicating that exosomes carrying RNA may play a role in mediating radiation-induced bystander effects and genomic instability (37).…”
mentioning
confidence: 78%
“…DNA damage was measured after addition of conditioned media to MCF7 cells and RNase was found to abrogate this DNA damage, indicating that exosomes carrying RNA may play a role in mediating radiation-induced bystander effects and genomic instability (37).…”
mentioning
confidence: 99%
“…The data represent AM ± SEM of three independent experiments. *p \ 0.05 compared to the pertinent control group oxygen species or cytokines and also by the release of microvesicles (Klammer et al 2015;Hei et al 2008;Kumar Jella et al 2014;Al-Mayah et al 2012). Furthermore, the importance of extracellular microvesicles in cancer treatment is gaining recognition as there is emerging evidence of their role in intercellular communication through which they influence the functioning of the nontargeted cells (El-Andaloussi et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Signals which cause damage of the neighboring cells can be released either through gap junctions (Azzam et al 1998) or as extracellular soluble substrates (Mothersill and Seymour 1998) and may be in the form of soluble substrates, such as reactive oxygen species (Klammer et al 2015) and cytokines (Hei et al 2008), or they may travel to the bystander cells via microvesicles (Kumar Jella et al 2014). Microvesicles are extracellular fragments of cell membrane containing different proteins, RNA molecules and other agents, which can influence various signaling pathways in the target cells, including pathways leading to oncogenesis, cell death or activation of the immune response (Al-Mayah et al 2012;Kumar Jella et al 2014).…”
Section: Introductionmentioning
confidence: 99%